Targeting the immuno-inflammatory-microbial network: a key strategy for sepsis treatment - Xu, Yue; Wang, Jiaxin; Yuan, Rui; Qin, Zhu; Long, Kunlan; Gao, Peiyang (Frontiers in Immunology, 2025)
Sepsis is a life-threatening condition caused by a dysregulated host response to infection, remaining a major global health challenge despite clinical advances. Therapeutic challenges arise from antibiotic misuse, incomplete understanding of its complex pathophysiology, and the unresolved interplay of immune dysregulation and microbiota disruption. Investigating microbial homeostasis in the shift from cytokine storm to immunosuppression may elucidate the interplay between microbial metabolites, immune dysfunction, and organ injury, providing a foundation for targeted therapies and drug development. Traditional Chinese Medicine (TCM) has demonstrated significant advantages in mitigating sepsis-associated cytokine storms and modulating gut microbiota homeostasis, offering a promising strategy for developing highly effective and less toxic targeted monomeric compounds. Elucidating the interactions within the immune-inflammation-microbiota network in sepsis paves the way for biomarker-driven personalized therapeutic approaches.